THE EFFECT OF FINGER PAINTING ON THE DEVELOPMENT OF CHILDREN’S CREATIVITY - Hayati, Zikra; Fajriah, Heliati; Jarmita, Nida; Oviana, Wati; Ovalia, Riska (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Based on the results of observations carried out at PAUD Ceria in August 2023, it was found that there were children aged 5-6 years who had problems with the development of creativity which were identified when the children were not able to complete the drawing task with the free theme given, when the drawing activity was in progress. progressing, the child does not look enthusiastic, and the child will imitate the example of the teacher's drawing shown, the child is not yet able to create different work from his friends. This research aims to find out whether there is an influence of finger painting in developing the creativity of children aged 5-6 years at PAUD Ceria Sabena Kids II Aceh Besar. The research uses a quantitative type with experimental methods, research design